Gender impact analysis and the taxation of retirement savings in Australia - Austen, Siobhan; Sharp, R.; Hodgson, Helen (Tax Institute of Australia, 2015)
Gender impact analysis of the tax transfer system makes gender issues in policies and budgets visible and enables their complexities to be revealed. By doing so, it facilitates the development of more equitable and efficient alternatives. This article provides a gender impact analysis of Australia's taxation and expenditure arrangements for superannuation and the age pension. By including both paid and unpaid work in the analysis, it identifies a number of critical features of the tax and transfer system that foster gender inequality. The article concludes that the gender impacts of the current policy on retirement savings and income should be addressed through a range of policy and budgetary changes. In particular, it advocates re-balancing the resourcing of superannuation tax concessions and the age pension, improving the rate of the age pension and removing the existing barriers to women's workforce participation that have been created by the income tax/family benefit system, including high childcare costs.